Harmony in Duality: Exploring the Philosophical Connections between Yin-Yang in Chinese Thought and Dualism in Western Philosophy - Abbas, Syed Tahir (PT FORMOSA CENDEKIA GLOBAL, 2024)
This comprehensive exploration delves into the intricate philosophical connections between Yin-Yang in Chinese thought and Dualism in Western philosophy, aiming to unravel the shared themes, distinctions, and contemporary relevance of these foundational concepts. The essay navigates the historical roots of Yin-Yang, tracing its origins in Chinese philosophy and unraveling its symbolic significance. Concurrently, it embarks on a journey through the evolution of Dualism in Western philosophical traditions, highlighting key figures and the development of dualistic thought. This section provides a nuanced understanding of how these concepts shape metaphysical perspectives, influencing cosmological frameworks and their applications in understanding reality. The exploration extends to the realm of ethics and morality, where Yin-Yang is examined for its emphasis on balance, harmony, and virtue, contrasting with the ethical dilemmas and moral dichotomies presented by Dualistic frameworks. The essay delves into the ethical implications of both philosophical systems, uncovering their unique contributions to moral philosophy. A comparative analysis section synthesizes the shared insights and differences between Yin-Yang and Dualism, offering a nuanced perspective on their respective approaches and applications. The examination considers their modern relevance, exploring how these philosophical concepts continue to influence contemporary thought and global perspectives. In conclusion, the abstract recaps the key points, emphasizing the richness of these philosophical traditions and their enduring impact on the understanding of existence, ethics, and the interconnected nature of reality.